Identification of Types of Ferns (Pteridophyta) in the STKIP Gotong Royong Masohi Environment - Sovian Sesca Elly; Rufiati Simal (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
Ferns (Pteridohyta) are cormophyte plants that have spores and are able to live in varying environmental conditions. The diversity of fern species can be identified through identification activities. Identification is the initial process in classifying a type of plant. Ferns are widely found in the STKIP Gotong Royong Masohi campus environment, but their species are not yet known. Therefore, this study aims to identify the types of ferns in the STKIP Gotong Royong Masohi campus environment. The type of research used is descriptive exploratory with a qualitative approach. This research was conducted in the STKIP Gotong Royong Masohi campus environment in August 2024. This research consists of 4 stages, namely the preparation stage, the sampling stage and the fern type identification stage. Based on the research results, it is known that there are 7 families and 9 types of ferns found in the STKIP Gotong Royong Masohi campus environment, namely Phymatosorus sclopendria, Cristella dentata, Asplenium nidus, Nephrolepis biserrata, Selaginella Sp, Pyrrosia lanceolata, Davallia denticulata, Lygodium flexuosum, and Pteris ensiformis.